2013
DOI: 10.3389/fonc.2013.00193
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Increase Drug Penetration in Solid Tumors

Abstract: Despite significant improvement in modalities for treatment of cancer that led to a longer survival period, the death rate of patients with solid tumors has not changed during the last decades. Emerging studies have identified several physical barriers that limit the therapeutic efficacy of cancer therapeutic agents such as monoclonal antibodies, chemotherapeutic agents, anti-tumor immune cells, and gene therapeutics. Most solid tumors are of epithelial origin and, although malignant cells are de-differentiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
123
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(124 citation statements)
references
References 184 publications
(252 reference statements)
0
123
0
1
Order By: Relevance
“…A longer serum-half life is a beneficial property of tumor-penetration promoting agents for their co-administered or conjugated drugs [1,49]. The TPP11 fusion to Fc did not compromise the serum half-life of Fc (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…A longer serum-half life is a beneficial property of tumor-penetration promoting agents for their co-administered or conjugated drugs [1,49]. The TPP11 fusion to Fc did not compromise the serum half-life of Fc (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…While the application of nanomedicines to cancer therapy can obviously boast success, more detailed scrutiny of the formulations has revealed that their large sizes may compromise their abilities to penetrate deep into a tumor mass [5,[8][9]. Thus, Torchilin and Jain disclosed in 1995 that tumor permeability was inversely proportional to NP radius [10].…”
mentioning
confidence: 99%
“…The folate receptor (FR) is a 38-kDa glycosylphosphatidylinositol anchored protein Comparison of nanoparticle penetration into solid tumors and sites of inflammation: studies using targeted and nontargeted liposomes [2,[16][17][18]. Because many cancer cell types overexpress FRs, it is possible to selectively target folate-derivatized cargoes to malignant cells within FR+ tumors [3,9,[18][19]. Similarly, because activated macrophages (but not resting macrophages or other hematopoietic cells) also overexpress FRs, folate-linked liposomes can also be targeted to sites of inflammation that characterize many autoimmune diseases [17,20].…”
mentioning
confidence: 99%
“…However, while therapeutic mAbs have had a high success rate in treatment of hematologic tumors, targeting solid tumors has been relatively difficult because of their lack of sufficient permeability (Choi et al 2013). Most solid tumors are derived from epithelial cells and their tissues pose significant barriers to drug penetration due to their high interstitial fluid pressure (IFP), high cell density, excessive deposition of extracellular matrix (ECM), and physical barriers composed of stroma proteins.…”
Section: Introductionmentioning
confidence: 99%